2020
DOI: 10.21203/rs.3.rs-26901/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The miR-200c/FUT4 axis prevents the proliferation of colon cancer cells by downregulating the Wnt/β-catenin pathway

Abstract: BackgroundMicroRNA(miR)-200c has been widely reported to be involved in colon cancer progress. However, the mechanisms of miR-200c in regulating tumor metastasis and growth remain to be fully elucidated. This study aimed to investigate the mechanism of miR-200c targets fucosyltransferase 4 (FUT4) on the proliferation of colon cancer.MethodsThe miR-200c and FUT4 mRNA levels in LoVo and SW480 cells were measured by real-time quantitative polymerase chain reaction. Further, miR-200c mimic, FUT4 siRNA and FUT4 mim… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…It is widely reported that miR-200c is involved in colon cancer progression. It has been reported that the overexpression of miR-200c inhibits the proliferation of colon cancer by targeting the FUT4/Wnt/ β-catenin pathway [26]. Our study showed that miR-200c overexpression in CRC could inhibit the activation of the downstream JNK signaling pathway and reverse drug resistance.…”
Section: Discussionsupporting
confidence: 52%
“…It is widely reported that miR-200c is involved in colon cancer progression. It has been reported that the overexpression of miR-200c inhibits the proliferation of colon cancer by targeting the FUT4/Wnt/ β-catenin pathway [26]. Our study showed that miR-200c overexpression in CRC could inhibit the activation of the downstream JNK signaling pathway and reverse drug resistance.…”
Section: Discussionsupporting
confidence: 52%